Organic Anion Transporter Polypeptide 1B1 Polymorphism Modulates the Extent of Drug–Drug Interaction and Associated Biomarker Levels in Healthy Volunteers. Issue 4 (13th April 2019) - Yee, Sook Wah; Giacomini, Marilyn M.; Shen, Hong; Humphreys, W. Griffith; Horng, Howard; Brian, William; Lai, Yurong; Kroetz, Deanna L.; Giacomini, Kathleen M.
Abstract : Understanding transporter‐mediated drug–drug interactions is an integral part of risk assessment in drug development. Recent studies support the use of hexadecanedioate (HDA), tetradecanedioate (TDA), coproporphyrin (CP)‐I, and CP‐III as clinical biomarkers for evaluating organic anion‐transporting polypeptide (OATP)1B1 (SLCO1B1) inhibition. The current study investigated the effect of OATP1B1 genotype c.521T>C (OATP1B1‐Val174Ala) on the extent of interaction between cyclosporin A (CsA) and pravastatin, and associated endogenous biomarkers of the transporter (HDA, TDA, CP‐I, and CP‐III), in 20 healthy volunteers. The results show that the levels of each clinical biomarker and pravastatin were significantly increased in plasma samples of the volunteers following administration of pravastatin plus CsA compared with pravastatin plus placebo. The overall fold change in the area under the concentration–time curve (AUC) and maximum plasma concentration (Cmax ) was similar among the four biomarkers (1.8–2.5‐fold, paired t ‐test P value < 0.05) in individuals who were homozygotes or heterozygotes of the major allele, c.521T. However, the fold change in AUC and Cmax for HDA and TDA was significantly abolished in the subjects who were c.521‐CC, whereas the respective fold change in AUC and Cmax for pravastatin and CP‐I and CP‐III were slightly weaker in individuals who were c.521‐CC compared with c.521‐TT/TC genotypes. In addition, this study provides the first evidence that SLCO1B1 c.521T>C genotype is significantly associated with CP‐I but not CP‐III levels. Overall, these results suggest that OATP1B1 genotype can modulate the effects of CsA on biomarker levels; the extent of modulation differs among the biomarkers.